Exploring macroevolution using modern and fossil data - Benton, Michael J. (Proc Biol Sci, 2015)
Macroevolution, encompassing the deep-time patterns of the origins of modern biodiversity, has been discussed in many contexts. Non-Darwinian models such as macromutations have been proposed as a means of bridging seemingly large gaps in knowledge, or as a means to explain the origin of exquisitely adapted body plans. However, such gaps can be spanned by new fossil finds, and complex, integrated organisms can be shown to have evolved piecemeal. For example, the fossil record between dinosaurs and Archaeopteryx has now filled up with astonishing fossil intermediates that show how the unique plexus of avian adaptations emerged step by step over 60 Myr. New numerical approaches to morphometrics and phylogenetic comparative methods allow palaeontologists and biologists to work together on deep-time questions of evolution, to explore how diversity, morphology and function have changed through time. Patterns are more complex than sometimes expected, with frequent decoupling of species diversity and morphological diversity, pointing to the need for some new generalizations about the processes that lie behind such patterns.